Navigating Behavioural Barriers to Fintech Chatbot Adoption: An Extended Innovation Resistance Theory Approach - Muhammed Jisham; Vanitha Selvaraj; Abin John (Colombo Business Journal)
The study explores the multifaceted dimensions of user resistance through the lens of the Extended Innovation Resistance Theory (IRT), providing insight into functional, psychological and behavioural inhibitors that prevent users from integrating fintech chatbot functionality into their financial management practices. This study employed a quantitative approach and conducted PLS-SEM to analyse the data collected from 286 fintech users. Findings suggest that behavioural inhibitors and IRT variables, except image barrier, play a critical role in preventing users from adopting fintech chatbots. This study emphasises the need to address these behavioural complexities to foster a more conducive environment for the integration of fintech chatbot technology into the financial services industry. A significant contribution of this research is that it introduces a behavioural dimension to the IRT to explore factors affecting the adoption of fintech chatbots, thus contributing to the existing literature on the user adoption and resistance of technology.